The narrative of sustainability and circular economy - A longitudinal review of two decades of research - Schöggl, Josef-Peter; Stumpf, Lukas; Baumgartner, Rupert J. (Resources, conservation and recycling, 2020)
•3822 journal papers on Circular economy (CE) between 2000 and 2019 are analyzed.•CE research exponentially grows but only slowly increases its thematic diversity.•Waste and recycling research and an economic and environmental focus dominate.•Higher value retention options and social sustainability form the periphery.•A subset relation between circular economy and sustainable development is indicated. Circular economy (CE) has gained momentum in the political, economic and scientific fields. The growing popularity of the concept is accompanied by some definitional ambiguities and conceptual uncertainties. In particular, the relationship and contribution of CE to sustainable development (SD) and thus to a more sustainable society is currently under discussion. The purpose of this paper is to contribute to this discussion by providing new insights into the evolution and state of CE research over the past two decades, in general, and its sustainability connotation, in particular. For doing so, a mixed-methods approach was adopted that combines a longitudinal bibliographic network analysis, multiple correspondence analysis and k-means clustering, correlated topic modeling, historiographic citation analysis and a semantic content analysis. The results indicate that the CE literature body can be divided into management and technically-oriented studies that have either a beginning-of-life or an end-of-life focus. Recycling is the most referred to R-strategy, followed by remanufacturing, repair and reuse, which, however, occur one order of magnitude less frequently. CE research and SD were found to exhibit a subset relationship, as only a limited number of environmental aspects is directly addressed. Social aspects form a periphery. The qualitative analysis further portraits the conceptual evolution of the CE-SD relationship between 2000 and 2019 by following the citation network of the 30 most influential CE papers. The results contribute to positioning CE research within the general Sustainable Development debate and to identifying potential, sustainability-related shortcomings and blind spots.